Comparison and correlation between polymer modified asphalt binders and mastics in high- and intermediate-temperature rheological behaviors. (18th January 2023) - Wang, Chao; Song, Lihao; Sun, Guoqiang
Graphical abstract: Highlights: Burgers model and damage mechanics-based crack model are applicable for polymer modified asphalt (PMA) materials. A two-stage crack growth model based on damage mechanics is proposed for PMA materials. Recovery percentage and delayed elastic perform good correlation between PMA binders and mastics. Fatigue life performs very significant correlation between PMA binders and mastics. Abstract: Traditional evaluation parameters for multiple stress creep recovery (MSCR) test and linear amplitude sweep (LAS) test are difficult to deeply and theoretically characterize the high- and intermediate-temperature rheological behaviors of polymer modified asphalt (PMA) binders and mastics. In this paper, one neat asphalt and four types of PMA binders and mastics are selected (i.e., the rubber modified ones, SBS modified ones, thermoplastic elastomer modified ones and SBS/Rubber modified ones). Two new analysis methods, i.e. Burgers model and damage mechanics-based crack growth model, are applied in analyzing the high- and intermediate-temperature rheological behaviors of PMA materials respectively. The Burgers model results indicate adding filler decreases the viscous deformation, and leads to lower non-recoverable compliance in the MSCR test. The polymer modification transfers the delayed elastic deformation to elastic deformation, thus causing more excellent rutting resistance. The damage mechanics-based crack growth model analysis reveals that adding filler enhances the crack growth rate and crack length, thus sacrificing the fatigue resistance. By contrast, the polymer modification enhances the fatigue resistance regardless of polymer types. Notably, a two-stage pattern based on crack growth rate and energy release rate was further proposed to identify the crack initiation and propagation of PMA materials. Specifically, 30% rubber modified asphalt binders and mastics perform best in both rutting and fatigue resistance. Moreover, PMA binders and mastics have strong correlation based on the recovery percentage and delayed elastic deformation. The correlation of fatigue life between PMA binders and mastics is very significant, however there was no obvious correlation in terms of crack length.